Liuzijue training improves hypertension and modulates gut microbiota profile - Wu, Sha; Zheng, Caiping; Liu, Nannan; Deng, Tingting; Wang, Jie; Qi, Luming; Xia, Lina (Frontiers in Cardiovascular Medicine, 2023)
Liuzijue (LZJ) exercise is a traditional exercise integrating breathing meditation and physical exercise, which can effectively prevent and treat hypertension. We aimed to evaluate the therapeutic effect of LZJ on hypertensive patients from the perspectives of blood pressure, vascular endothelial function, immune homeostasis, and gut microbiota. We conducted two randomized, controlled, double-blind experiments to compare LZJ and aerobic training (AT) for 12 weeks in 41 hypertensive patients. We measured the blood pressure level, vascular endothelial function, serum inflammatory factor concentration, and fecal microbial composition of hypertension patients. Compared with AT, LZJ has a more significant effect on serum inflammatory factors (IL-6 and IL-10) and gut microbiota. PCoA analysis showed that LZJ tended to transform the gut microbiota structure of hypertensive subjects into that of healthy people. This process involves significant changes in Bacteroides, Clostridium_sensu_stricto_1, Escherichia-Shigella, Haemophilus, Megamonas, and Parabacteroides. especially Bacteroides and Escherichia-Shigella, which are closely related to the improvement of blood pressure in hypertensive patients. In conclusion, our results confirm that LZJ can be used as an adjuvant treatment for hypertensive patients, which can effectively reduce blood pressure patients, improve the immune homeostasis and gut microbiota structure in patients, and provide a theoretical reference for the use of LZJ in the clinic.